Actualidad de la crítica de Karl Polanyi a la sociedad de mercados - Maya Ambía, Carlos Javier (Política y Cultura, 2014)
Karl Polanyi's critique of market society is a very powerful tool for understanding our current social reality. It helps us to formulate a creative and purposeful proposal that contributes to build a just, equitable, and more humane society, that would be committed to the future life on the planet. A comparison between the society criticized by Polanyi and ours, leads us to discover the validity of his basic concepts and his method for the preparation of a new critical discourse that not only takes advantage of the legacy of the author, but also expands, clarifies and updates it. (English)
Sociology
Keywords: crítica social; doble movimiento; double movement; market society; mercado autorregulado; self-regulated market; social critique; sociedad de mercado

Una lectura transversal de la Formación Profesional Ocupacional pública: entre Karl Polanyi, Max Weber y Michel Foucault - Dautrey, Philippe (Cuadernos de Trabajo Social (Espana) Vol. 22, 2009)
La formación profesional ocupacional (FPO) se ubica en una encrucijada de problemáticas que analizaron tanto Karl Polanyi como Max Weber y Michel Foucault. Por un lado, el papel fundamental que desempeñan los mercados autorregulados en el nuevo gran cambio que significa la globalización suscita un movimiento contraprotector del que participa esta capacitación para el empleo. Por otro, respalda el desarrollo de la organización racional capitalista, la cual a su vez implica su racionalización. Por último, es parte del control social que tal organización necesita para llevar a cabo sus propósitos. En resumen, las todavía relevantes obras de dichos estudiosos ofrecen una perspectiva diacrónica sobre el entorno de la FPO. También permiten apreciar el papel equívoco que ésta cumple respecto al desenvolvimiento y a los valores del sistema socio-económico vigente. ENG: The occupational vocational training (FPO) is located at a crossroads of problems that analyzed both Karl Polanyisuch as Max Weber and Michel Foucault. On the one hand, the fundamental role played by self-regulated markets in the new great change that globalization means provokes a counterprotective movement in which this training for employment is involved. On the other, it supports the development of rational capitalist organization, which in turn implies its rationalization. Finally, it is part of the social control that such organization needs to carry out its purposes. In summary, the still relevant works of these scholars offer a diachronic perspective on the environment of the FPO. They also allow us to appreciate the equivocal role it plays in respect to the development and values ​​of the current socio-economic system.
Sociology
Keywords: FOUCAULT; Michel; 1926-1984; Post-Fordism; Spain; WEBER; Max; 1864-1920; capitalism; capitalismo; control social; employment; formacion profesional; knowledge economy; racionalizacion de la economia; rationalization of the economy; social control; vocational training; work

Karl Polanyi o la humildad de las ciencias sociales - Rendueles, César (NEXO. Revista de Filosofía, 2004)
EN: This essay proposes a periodization of Karl Polanyi’s work, from his early writings in Vienna to his anthropological work developed in the context of the substantivist-formalist discussion. The outstanding feature of this studies is the way they combine empirical sharpness with epistemological modesty. Unlike orthodox economy and imperialism theories, Polanyi doesn’t ignore the precarious theoretical situation of social science. His investigations are based on empirical thesis both broadly accepted and heuristically productive. Este artículo analiza las distintas fases de la obra de Karl Polanyi, desde sus pri- meros escritos en Viena a su obra antropológica en el contexto del debate entre sus- tativistas y formalistas. La principal virtud de estos estudios es su mezcla de acier- to empírico y modestia epistemológica. A diferencia de la economía ortodoxa o de las teorías del imperialismo, Polanyi no rehuye la precaria situación teórica de las ciencias sociales. Sus investigaciones se basan en tesis empíricas ampliamente aceptadas que, sin embargo, demuestran una notable vitalidad heurística.
Sociology
Keywords: Karl Polanyi; epistemology; periodization; social science